Occupational COVID-19 Prevention among Congolese Healthcare Workers: Knowledge, Practices, PPE Compliance, and Safety Imperatives - Nzaji Michel-Kabamba; Nlandu Roger Ngatu; Ngombe Leon-Kabamba; Astrid Katumbo-Mukemo; Olivier Mukuku; Jean Ngoyi-Mukonkole; Guillaume Ngoie-Mwamba; Elie Kilolo-Ngoie; Ignace Bwana-Kangulu; Dora Kafusthi-Mukemo; Deca Blood Banza-Ndala; Denis Kabila-Mutombo; et al. (Tropical Medicine and Infectious Disease, 2020)
The SARS-CoV-2 (COVID-19) pandemic has had a tremendous impact on the functionality of health systems and world affairs. We assessed knowledge, attitudes, and practices (KAPs) of healthcare workers (HCWs) in the Democratic Republic of the Congo (DRC). This was a cross-sectional study conducted in 23 referral hospitals located in three towns of the DRC (Lubumbashi, Kamina, Mbuji-Mayi). In total, 613 HCWs were surveyed using the World Health Organization’s (WHO’s) “Exposure Risk Assessment in the Context of COVID-19” questionnaire. Participants included medical doctors (27.2%) and other categories of HCWs (72.8%). The mean age was 40.3 ± 11.7 years. Over 80% (range: 83–96%) of respondents had sufficient knowledge on each of the three domains: COVID-19 symptoms, disease transmission, and patient care approach. However, attitudes and practices scores were relatively low. Only 27.7% of HCWs were willing to receive a COVID-19 vaccine when it is available, whereas 55% of HCWs complied with good practices; 49.4% wore masks consistently and, surprisingly, only 54.9% used personal protective equipment (PPE) consistently at work and during contact with patients. Knowledge level was positively associated with the use of social media as a primary source of COVID-19-related information and the category of residence, with HCWs from towns already affected by the COVID-19 epidemic being more likely to have positive attitudes (adjusted OR, 1.64; 95%CI, 1.32–2.20) and comply with good practices (aOR, 2.79; 95%CI, 1.93-4.06). This study showed that most Congolese HCWs had sufficient knowledge on COVID-19, whereas the majority did not comply with consistent PPE use. The government of the DRC should urgently take major steps in capacity building for HCWs in outbreak preparedness and supplying hospitals with PPE.